ANALISIS BAHAYA LONGSOR DI KECAMATAN BAYANG UTARA KABUPATEN PESISIR SELATAN SUMATERA BARAT - Mona Adria Wirda (Universitas Negeri Medan, 2016)
This research was conducted because of insuitaibility of land management with geographicaland klimatological region that cause the higher potention of landslide in Kecamatan BayangUtara, Kabupaten Pesisir Selatan Sumatera Barat. The purpose of this research is to explainareas level of landslide and to describe a map of guidance of landuse depending of the level oflandslide. This research is a descriptive research that was conducted in two stages by usingPaimin et al method and by Geographic Information System (GIS) Arc Gis 9.3. The 10samples of research was determined by purposive sampling based on differentiation of landunit in Bayang Utara. The data of this research was land units, topographic, geology, soil,landuse, coordinate, and maps.The results of this research are : (1) there were 2 levels ofdanger of landslide which were medium level in V1 I Tomp Glei Saw , V3 III Qv Kam Hut,and V5 V tomp kam hut; and high level in V5 V Tomp Kam Sem, V5 V Qv Kam Hut Sek,V5 V Qv Kam Teg, and V5 V Pb Kam Hut, V5 V Qou Kam Hut, V4 IV Tqr Kam Hut andV5 V Qv Kam Hut; (2) there were 2 directions of landuse which were zone with mediumlevel of landslide for buffer zone; and zone which were hig level of landslide for conservationarea.Key word : Landslide, Level of Danger of Landslide